Keanekaragaman Dan Kelimpahan Gastropoda Di Zona Intertidal Pantai Kota Dua Kecamatan Larantuka Kabupaten Flores Timur Sebagai Media Pembelajaran Biologi SMA Berupa Video - Lamalouk, Maria Elisabeth T; Seran, Lukas; Nau, Getrudis Wilhelmina (Program Studi Pendidikan Biologi, 2025)
Kota Dua Beach is a tourist destination located in East Sarotari Village, Larantuka District, East Flores Regency. Until now, the number and types of gastropods in the intertidal zone of Kota Dua Beach are not yet known. The aim of this research is to determine the diversity and abundance of gastropod species on Kota Dua Beach and develop biology learning media in the form of videos. This research is development research using the ADDIE model. 17 species of gastropods were found, namely Haliotis squamata, Conus miles, Conus rosiae, Bostycapulus aculeatus, Cypraea tigris, Cypraea annulus, Tenguella granulate. Platydoris cruenta, Onchidium melakense, Patella caerulea, Trochus maculates, Turbo cornutus, Astralium calcar, Cypraea talpa, Lunella smaraga, Muricanthus nigritus and Cellana nigrolineata. The diversity index of 2.714527275 is in the medium category. The highest species abundance index was 0.85 ind/m², while the lowest was 0.1 ind/m². The results of video validation by media experts reached a percentage of 71.76%, and by material experts, 93.33% with an average of 82.54% categorized as very valid as learning media. The conclusion of this research is as follows: 17 species of gastropods were identified at Kota Dua Beach with a diversity index in the medium category, the highest species abundance was 0.80 ind/m², and the video developed about the diversity and abundance of gastropods at Kota Dua Larantuka Beach is classified as valid for use as a learning medium.